The Effect of Brain Based Learning on Improving Students Critical Thinking Ability and Self Regulated - Maryati, Sarifah Sari; Purwanti, Irma; Mubarika, Melinda Putri (IJIS Edu : Indonesian Journal of Integrated Science Education, 2020)
This research is motivated by the low ability of mathematical critical thinking and Self Regulated Cimahi 10 Public Middle School students, so that a learning approach is needed to overcome these problems. The alternative approach applied is the Brain Based Learning Model approach.The objectives of this researcher are: 1) to examine students' mathematical critical thinking skills; 2) reviewing the Self Regulated attitude of students who obtain Brain Based Learning learning with students who have expository learning; 3) examine there is a positive correlation between Critical Thinking with Self Regulated students who obtain Brain Based Learning and expository learning. The population in this study was grade VII students of SMP Negeri 10 Cimahi. The samples in this study were class VII-B (Brain Based Learning) and class VII-D (expository). The instruments used in this study were the Critical Thinking test and the student's Self Regulated questionnaire. The test used is a subjective type test (description). The way to analyze data is with IBM SPSS Statistics 18.0 for Windows. The results showed that: 1) the mathematical critical thinking ability of students who obtained learning based on the Brain Based Learning approach was better than students who gained expository learning; 2) Self Regulated attitude, students who get Brain Based Learning are better than students who get expository approach learning; 3) there is no correlation between critical thinking with Self Regulated students who obtain Brain Based Learning and expository learning.